Purinergic Receptors in Adipose Tissue As Potential Targets in Metabolic Disorders - Tozzi, Marco; Novak, Ivana (Frontiers in Pharmacology, 2017)
Extracellular nucleosides and nucleotides, such as adenosine and adenosine triphosphate (ATP), are involved in many physiological and pathological processes in adipose tissue. It is becoming accepted that, in addition to the well-established sympathetic and hormonal system, purinergic receptors contribute significantly to regulation of adipocyte functions. Several receptor subtypes for both adenosine (P1) and ATP (P2X and P2Y) have been characterized in white and brown adipocytes. The effects mediated by adenosine and ATP on adipocytes are multiple and often differing, depending on specific receptors activated. Using a variety of agonists, antagonists and transgenic animals it has been demonstrated that adenosine and P2 receptors are involved in lipolysis, lipogenesis, adipokines secretion, glucose uptake, adipogenesis, cell proliferation, inflammation and other processes. Given their central role in regulating many adipose tissue functions, purinergic receptors are considered potential therapeutic targets in different pathological conditions, such as obesity and type-2 diabetes. To achieve this goal, specific and potent P1 and P2 receptors activators and inhibitors are being developed and show promising results. However, more insight is needed into the function of P2 receptors in brown and beige adipocytes and their potential role in thermogeneis. This review aims at summarizing current knowledge on the patho-/physiological role of P1, P2X and P2Y receptors in white and brown adipocytes and their potential exploitation for pharmacological intervention. Furthermore, we analyze impact of purinergic signaling in adipose tissue - in health and metabolic diseases.